An engineered superantigen SEC2 exhibits promising antitumor activity and low toxicity - Xu, Mingkai; Wang, Xiaogang; Cai, Yongming; Zhang, Huiwen; Yang, Hongli; Liu, Changxiao; Zhang, Chenggang (Cancer Immunology, Immunotherapy, 2011)
Recent studies suggested that the histidine residues at 118 and 122 play an important role for the toxicity of staphylococcal enterotoxin C subtype 2 (SEC2), and the substitutions of both histidines with alanine can severely impair the fever activity of SEC2. We hypothesized that promising SEC2 antitumor agent with low toxicity and enhanced superantigen activity can be constructed by introducing related mutations at protein functional sites of SEC2. We showed that the SEC2 mutants H122A and H118A/H122A exhibited improved superantigen activity after introducing the point mutations at Thr20 and Gly22. A resultant mutant, named as SAM-3, has considerable abilities to inhibit the growth of H22 and Hepa1-6 tumor cells in vitro and colon 26 solid tumor in vivo. Furthermore, SAM-3 also exhibits significantly reduced toxicity compared with native SEC2. The study provides a novel strategy for designing promising superantigen immunotherapeutic agent. The constructed SEC2 mutant SAM-3 can be used as a powerful candidate for cancer immunotherapy and could compensate the deficiency caused by toxicity of native SEC2 in clinic.